Woven Endobridge Embolization Versus Microsurgical Clipping for Unruptured Anterior Circulation Aneurysms: A Propensity Score Analysis. Issue 4 (28th December 2020) - Goertz, Lukas; Liebig, Thomas; Siebert, Eberhard; Pennig, Lenhard; Laukamp, Kai Roman; Celik, Erkan; Timmer, Marco; Brinker, Gerrit; Schlamann, Marc; Goldbrunner, Roland; Dorn, Franziska; Krischek, Boris; et al.
Abstract: BACKGROUND: Intrasaccular flow-disruption represents a new paradigm in endovascular treatment of wide-necked bifurcation aneurysms. OBJECTIVE: To retrospectively compare Woven Endobridge (WEB) embolization with microsurgical clipping for unruptured anterior circulation aneurysms using propensity score adjustment. METHODS: A total of 63 patients treated with WEB and 103 patients treated with clipping were compared based on the intention-to-treat principle. The primary outcome measures were immediate technical treatment success, major adverse events, and 6-mo complete aneurysm occlusion. RESULTS: The technical success rates were 83% for WEB and 100% for clipping. Procedure-related complications occurred more often in the clipping group (13%) than the WEB group (6%, adjusted P < .01). However, the rates of major adverse events were comparable in both groups (WEB: 3%, clip: 4%, adjusted P = .53). At the 6-mo follow-up, favorable functional outcomes were achieved in 98% of the WEB embolization group and 99% of the clipping group (adjusted P = .19). Six-month complete aneurysm occlusion was obtained in 75% of the WEB group and 94% of the clipping group (adjusted P < .01). CONCLUSION: Microsurgical clipping was associated with higher technical success and complete occlusion rates, whereas WEB had a lower complication rate. Favorable functional outcomes were achieved in ≥98% of both groups. The decision to use a specific treatment modality should be made on an individual basis and in accordance with the patient's preferences. Graphical Abstract: